Memory, trauma treatment, and the law - Brown, Daniel P. 1948-; Scheflin, Alan W.; Hammond, D. C. (A Norton professional book, 1998)
The authors critically review memory research, trauma treatment, and legal cases pertaining to the false memory controversy. They discuss current memory science and research with both children and adults, pointing out where findings are and are not generalizable to trauma memories recovered in psychotherapy. This is an essential reference on memory for all clinicians, researchers, attorneys, and judges